God image handbook for spiritual counseling and psychotherapy research, theory, and practice - Moriarty, Glendon; Hoffman, Louis (Haworth Pastoral Press, 2008)
God Image Handbook for Spiritual Counseling and Psychotherapy: Research, Theory, and Practice comprehensively discusses the psychodynamic foundation and research that contribute to the understanding of the God image, and then presents seven different theoretical and technical approaches to help those who have personal and religious problems. Case examples illustrate how the God image changes through the therapy process. The guidebook also explores future developments and the implications of race, culture, gender orientation, and economic conditions that impact the God image.